Original articleCCL2 (MCP-1) and CCL5 (RANTES) levels in the peripheral blood of multiple sclerosis patients treated with Glatiramer Acetate (Copaxone) - Losy, Jacek; Michałowska-Wender, Grażyna; Kudryńska, Aleksandra; Wender, Mieczysław (Folia Neuropathologica, 2005)
The MCP-1 and RANTES levels were measured in 20 multiple sclerosis patients before and after 1 year daily treatment with 20 mg of subcutaneously applied glatiramer acetate. The level of MCP-1 in serum from multiple sclerosis patients was lower than in control subjects. After one year of therapy with glatiramer acetate, the level of MCP-1 was almost identical with that at the starting point. The concentration of RANTES in MS, both before and after therapy, did not differ from the control subjects. The results emphasise the marked difference between the influence of glatiramer acetate and IFNβ-1a on the expression of the studied cytokine. Glatiramer acetate therapy in multiple sclerosis is not so much an effective as a protective factor of antiinflammatory cytokines, it should be regarded as a down-regulator of proinflammatory agents.